Killer acquisitions and beyond: Policy effects on innovation strategies - Igor Letina; Armin Schmutzler; Regina Seibel (University of Zurich, Department of Economics, 2023)
This paper provides a theory of strategic innovation project choice by incumbents and start-ups which serves as a foundation for the analysis of acquisition policy. We show that, in spite of countervailing incentives on incumbents and entrants, prohibiting acquisitions has a weakly negative overall innovation effect. We provide conditions determining the size of the effect and, in particular, conditions under which it is zero. We further analyze the effects of less restrictive policies, including merger remedies and the tax treatment of acquisitions and initial public offerings. Such interventions tend to prevent acquisitions only if the entrant has sufficiently high stand-alone profits.
hdl:10.5167/uzh-189748
Keywords: O31; L41; G34; 330; innovation; killer acquisitions; merger policy; potential competition; start-ups